Distribution of phylogenetic groups, sequence type ST131, and virulence‐associated traits among Escherichia coli isolates from men with pyelonephritis or cystitis and healthy controls. (7th February 2013) - Kudinha, T.; Johnson, J. R.; Andrew, S. D.; Kong, F.; Anderson, P.; Gilbert, G. L.; Tassies, P.
Abstract Urinary tract infections (UTI), which are mostly caused by Escherichia coli, are an important public health problem worldwide. Although men experience diverse UTI syndromes, there have been relatively few molecular‐epidemiological studies of UTI pathogenesis in men. We studied the distribution of 22 E. coli virulence factor (VF) genes, major phylogenetic groups, sequence type ST131, and UTI‐associated O antigens among 101 pyelonephritis, 153 cystitis and 135 fecal healthy control E. coli isolates from men aged 30–70 years in a regional area of NSW, Australia. Overall, the studied traits exhibited a prevalence gradient across these groups, highest in pyelonephritis, intermediate in cystitis, and lowest among fecal isolates. Differences in virulence gene prevalence between cystitis and pyelonephritis isolates were limited to eight genes. The UTI‐associated O antigens were also distributed widely, but types O6, O25 and O75 were significantly associated with pyelonephritis. The ST131 clonal group, which accounted for 13% of isolates overall (22% of group B2 isolates), likewise exhibited a significant descending prevalence gradient from pyelonephritis (36%), through cystitis (8%), to fecal (0%) isolates. These findings contribute to better understanding of the pathogenesis of UTIs in men and identify specific VF genes and O types, and a prominent clonal group (ST131), as being important in UTI pathogenesis in this population.